Strategi Pengelolaan Pariwisata Pantai Prigi Dalam Upaya Mendorong Pertumbuhan Ekonomi Berkelanjutan Di Masyarakat Lokal - Mahila Zahra; Mei linda Nurhalimah; Hodri Fungkiuudin (Lembaga Pengembangan Kinerja Dosen, 2024)
Trenggalek Regency is a regency located on the south coast and has enormous potential for beach tourism. Coastal areas are areas that have the potential to be developed, one of which is Prigi Beach. Prigi Beach is one of the tourism destinations that is considered promising. Prigi Beach, located in Watulimo District, Trenggalek Regency, is one of the tourism destinations that offers significant opportunities for sustainable economic growth for local communities. However, to achieve this, an appropriate and good management strategy is needed. This research was conducted to find out and also analyze effective management strategies for Prigi Beach to encourage sustainable economic growth for local communities. The existence of an appropriate and good strategy is expected to provide significant economic benefits for local communities.